Concept of MORALITY in Authorial Worldview: An Analysis of B. Pilnyak's Novel “The Volga Flows into the Caspian Sea” - Dubova, M. A. (Nauc̆nyj dialog (Online), 2025)
This article examines the concept of MORALITY as presented in B. Pilnyak's novel “The Volga Flows into the Caspian Sea.” It is explored as a world-modeling universality that unfolds in relation to the author's persona, the character system, and the motif paradigm within the narrative. The relevance of this study is underscored by its focus on the linguistic and stylistic expressions of world-modeling universals in literary texts. Employing methods of philological, semantic, linguistic-stylistic, and conceptual analysis, the author investigates the field structure of the concept of MORALITY within the text and arrives at conclusions that reveal its connections to the leitmotifs of life and death, labor, among others. A distinctive status of love is identified within the spectrum of moral concepts in the novel and in the author’s system of life values. The article characterizes lexemes that objectify the poles of the binary semantic opposition “moral — immoral” and related dichotomies. Techniques of analogy, allegory, spatial-temporal plane merging, and repetition are identified and commented upon as they represent the author's “voice” in the text. The continuity of moral values that objectify the concept of MORALITY in both the authorial and national worldview is substantiated through an exploration of the imagery system of the work, particularly focusing on Professor Poletika and his daughter Lyubov.